2010
DOI: 10.1007/s10694-010-0167-8
|View full text |Cite
|
Sign up to set email alerts
|

Conductive and Radiative Heat Transfer in Ceramic and Metal Foams at Fire Temperatures

Abstract: In addition to the multiple actual or possible applications of metal and ceramic foams in various technological fields, their thermal properties make them a good candidate for utilization as fire barriers. Several studies have shown experimentally their exceptional fire retardance due to their low apparent thermal conductivity. However, while the thermal properties of this porous material have been widely studied at ambient temperature and are, at present, well-known, their thermal behaviour at fire temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 40 publications
0
42
0
1
Order By: Relevance
“…As the effective properties significantly depend on the geometry of the porous media, accurate computational approaches directly incorporate the exact morphology using, for example, computed tomography of the materials of interest [4][5][6][7][8]. There have been attempts to summarize effects of conduction and radiation into one single parameter sometimes referred to as ''phononic diffusivity" [9,10] or ''equivalent conductivity" [11]. This parameter must, by definition, heavily depend on temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the effective properties significantly depend on the geometry of the porous media, accurate computational approaches directly incorporate the exact morphology using, for example, computed tomography of the materials of interest [4][5][6][7][8]. There have been attempts to summarize effects of conduction and radiation into one single parameter sometimes referred to as ''phononic diffusivity" [9,10] or ''equivalent conductivity" [11]. This parameter must, by definition, heavily depend on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, no quantification is given for a realistic case and the importance of the different terms under various conditions is not given in [14]. Coquard et al [11] stated that in the case of ''metal or ceramic open cell foams" they have ''checked from numerous results obtained on different cellular structures with various optical properties that this coupling is relatively weak". Their findings suggest that for some setups the superposition of the results obtained for the two modes separately is justified without giving more details.…”
Section: Introductionmentioning
confidence: 99%
“…Three simplified models were used, one based on the assumption that conduction through the solid material can be either in series or parallel. A simple scaling expression was also used, along with D model [8,15,36], and an analytical model based on the numerical and 3D tomographic structure parameters in terms of ratio between the thickness of the struts and the nodes (referred to as lumps in the originating work, and preserved in the notation here, D st /d lu ) and the node shape [18]. Two empirical expressions for high porosity (> 90%) foams are also compared to our experimental measurements.…”
Section: Validity With Correlations and Modelsmentioning
confidence: 99%
“…Strategies that go beyond simplified unit cell structures have been explored, for example, by analysing the real foam structure obtained from 3D computed tomography [12] to observe its effects on the ETC. This can support the development of more accurate generic correlations [10,12,18], but is limited by the small volumes of foams that can be investigated in this way. A review of the wide range of theoretical and empirical approaches for porous metals found that each model defines a specific morphology and is hence of limited applicability to other types [11,12,18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation